The study on the effect of laser power on kerf width for carbon dioxide laser cutting process - Ahmad Shahrul Amrie, Mohd Supri (2012)
This study focuses on the effect of laser power on kerf width using CO2 laser machine. The experiment was conducted by using laser cutting process on 2.5 mm thick of acrylic sheet. The laser cutting parameters considered include laser power and cutting speed. The good cut quality for laser cutting process has a uniform with smaller kerf width. The effect of the laser cutting parameter on the cut quality was further investigated by monitoring the kerf width using image analyzer. After performed the experiment and analysis it shows that the lower laser power and higher cutting speed produce narrower kerf width.